Stigmatic receptivity and hybridization in cowpea beans (Vigna unguiculata L. (Walp.)) - Araméndiz-Tatis, Hermes; Cardona-Ayala, Carlos; Espitia-Camacho, Miguel; Hernández-Murillo, Jenry Rafael (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Classic plant breeding, based on the selection of superior individuals and directed crosses, led to the need-to-know aspects of the floral biology of cowpea beans. The research was carried out at the Universidad de Córdoba, Colombia, through two experiments: in the first, stigmatic receptivity was evaluated as response time to hydrogen peroxide, under a randomized complete block design, with a 3×4 factorial arrangement (three genotypes: Caupicor 50, Missouri and BRS Milenium, and at four hours of the day: 7:00 and 9:00 AM; 3:00 and 5:00 PM) and three replications. In the second, the percentage of viable crosses was evaluated, under a randomized complete block design, with a 2×2 factorial arrangement (two crosses: Missouri × IT86 and Missouri × BRS Milenium, and two methods: 1 (morning) and 2 (afternoon), and four replications. The greatest stigmatic receptivity was recorded in the BRS Milenium and Missouri genotypes with a time of 3.28±0.07 and 2.01±0.12 min at 7:00 and 9:00 AM, while Caupicor 50, time of 1.80±0.09 min at 3:00 PM. The artificial hybridizations carried out in the morning (method 1) registered the highest viable crosses, 78.6% in Missouri × BRS Milenium and 57.1% in Missouri × IT86. Therefore, artificial hybridizations should be done in the morning due to a more favorable environment for pollen grain germination, given the greater stigmatic receptivity.